Kesesuaian ASEAN Agreement on Transboundary Haze Pollution (AATHP) dengan Norma ASEAN - Miftahul Choir (Jurnal Sentris, 2018)
Haze pollution is one of the challenges that ASEAN has faced from several decades. Indonesia, as the country that hold most of the tropical forestry in the region, occasionally had forest fire that caused by either climate change or man-made deforestation. Forest fire that occurred in Indonesia consequences at thick haze in neighboring countries Malaysia and Singapore skies, which madeboth countries securitize as it was threatening the lives of their people. Thus, in order to tackle the problem, on 2002, ASEAN released an environmental protocol named ASEAN Agreement of Transboundary Haze Pollution (AATHP). However, the questions raises whether the enviromental protocol fit to the ASEAN Way. This paper argues that AATHP is not violating any of ASEAN norms and value, as it is not a fully legally binding protocol. Constructivism approach will be used as a tool to analyse how AATHP comply to ASEAN way.